2009
DOI: 10.1074/jbc.m809752200
|View full text |Cite
|
Sign up to set email alerts
|

HSCARG Regulates NF-κB Activation by Promoting the Ubiquitination of RelA or COMMD1

Abstract: The redox sensor protein HSCARG translocates from the cytoplasm to the nucleus in response to decreased cellular NADPH or increased nitric oxide, and is involved in protein regulation. However, the regulatory mechanism of HSCARG has remained elusive. In this report, through a yeast two-hybrid screen, HSCARG was found to associate with the copper metabolism gene MURR1 domain containing protein 1 (COMMD1), an inhibitor of NF-B, and negatively regulate COMMD1 by accelerating its ubiquitination and proteasome-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…In contrast, there were no differences in TLR4 expression. It has been reported that when cellular NADPH levels are low, the NADPH sensor protein NMRAL1 (NmrA-like family domain-containing protein 1) translocates to the nucleus and targets p65 for degradation and furthermore releases COMMD1 (copper metabolism gene MURR1 domain containing protein 1) to inhibit NF-κB (Lian and Zheng, 2009; Zheng et al, 2007). As this protein may link increased NADPH levels to the pro-inflammatory phenotype, we determined regulation of NMRAL1 in cytosolic and nuclear fractions in Stamp2 −/− cells.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, there were no differences in TLR4 expression. It has been reported that when cellular NADPH levels are low, the NADPH sensor protein NMRAL1 (NmrA-like family domain-containing protein 1) translocates to the nucleus and targets p65 for degradation and furthermore releases COMMD1 (copper metabolism gene MURR1 domain containing protein 1) to inhibit NF-κB (Lian and Zheng, 2009; Zheng et al, 2007). As this protein may link increased NADPH levels to the pro-inflammatory phenotype, we determined regulation of NMRAL1 in cytosolic and nuclear fractions in Stamp2 −/− cells.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, AS is inhibited and NO production decreased. 3,61,62 Translocation of HSCARG from the cytoplasm to the nucleus has also been shown to terminate activation of transcription factor NF-κB, 63 thereby establishing a close link between the cellular redox state and gene regulation. NAD(P) has also been implicated in regulation of circadian rhythms.…”
Section: Regulatory Role Of Nadpmentioning
confidence: 98%
“…XIAP (Burstein et al 2004; Maine et al 2009), HSCARG (Lian and Zheng 2009), Clusterin (Zoubeidi et al 2010), and ARF (Huang et al 2008) were identified as COMMD1 interacting proteins regulating several components of this process.…”
Section: Molecular Function Of Commd1mentioning
confidence: 99%